Dairy Supply Chain: A Vensim based Conceptual Model - Nasir, Tasnuba; Quaddus, Mohammed; Shamsuddoha, Mohammad (Institute for Research and Community Service, Petra Christian University, 2013)
The emphases on supply chain have increased in recent years among academia and industry circle. In this paper, supply chain model was developed based on a case dairy farm under the Vensim environment. System dynamics and case method under positivist and quantitative paradigm were used to develop simulation model. The objectives of this paper was to develop causal/qualitative model then transform into quantitative model. This paper is a conceptual model to see dairy supply chain structure and also find out the direction for further development of the current operation in simulation environment. Discussion were based on simulation supply chain model both qualitative and qualitative format.